Triradiate cartilage fracture of the acetabulum treated surgically: Triradiate cartilage fracture - Spina, Mauro; Luppi, Valentina; Chiappi, Jacopo; Bagnis, Francesco; Rocca, Guido (Acta Biomedica Atenei Parmensis, 2019)
Fractures of the acetabulum are rare in the pediatric age and may be complicated by the premature closure of the triradiate cartilage. We report a case of triradiate cartilage displaced fracture treated surgically. A 14 years old boy, following a high-energy road trauma, presented an hematoma in the right gluteal region with severe pain. According to radiographic Judet’s projections was highlighted a diastasis of the right acetabular triradiate cartilage.  CT scan study with 2D-3D reconstructions confirmed as type 1 Salter-Harris epiphyseal fracture. Due to the huge diastasis of the triradiate cartilage, the patient was operated after 72 hours through a plating osteosynthesis. We decided during the preoperative study that the plates should not be removed. Two years after surgery, the patient is clinically asymptomatic; the radiographic evaluation shows a complete cartilage’s fusion and the right acetabulum is perfectly symmetrical to the contralateral. For the treatment of acetabular fractures in pediatric age should be carefully evaluated fracture’s pattern, patient’s age, skeletal maturity’s grade, acetabulum’s volume and diameter.